Energetic design of grain boundary networks for toughening of nanocrystalline oxides. Issue 12 (September 2018) - Bokov, Arseniy; Zhang, Shenli; Feng, Lin; Dillon, Shen J.; Faller, Roland; Castro, Ricardo H.R.
Graphical abstract: Abstract: Improving the mechanical performance of nanocrystalline functional oxides can have major implications for stability and resilience of battery cathodes, development of reliable nuclear oxide fuels, strong and durable catalytic supports. By combining Monte Carlo simulations, experimental thermodynamics, and in-situ transmission electron microscopy, we demonstrate a novel toughening mechanism based on interplay between the thermo-chemistry of the grain boundaries and crack propagation. By using zirconia as a model material, lanthanum segregation to the grain boundaries was used to increase the toughness of individual boundaries and simultaneously promote a smoother energy landscape in which cracks experience multiple deflections through the grain boundary network, ultimately improving fracture toughness.